The Jewish minority in the Second Polish Republic: the activities of the Board of the Jewish Community in Lvov during the years 1919-1924 = Mniejszość żydowska w II Rzeczypospolitej Polskiej: działalność Zarządu Gminy Wyznaniowej Żydowskiej we Lwowie w latach 1919-1924 - Koziński, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to analyze data on the functioning of the Jewish Community in Lvov during the years 1919-1924. The indicated problems will enable to show the functioning of the Jewish minority in the conditions of the reviving Polish state - both in socio-political terms, and in the organizational aspect. It is particularly important to show the Jewish minority opinion about the conditions of Second Polish Republic. Additionally, this article will help restore the memory of the individual members of the Jewish community in Lvov.
Keywords: national issue; Jews; The Second Republic of Poland; kwestia narodowa; Żydzi; II (druga) Rzeczpospolita